PENDAMPINGAN MANAJEMEN PENGELOLAAN SAMPAH RUMAH TANGGA DI KELURAHAN SAMBIROTO, KECAMATAN TEMBALANG, KOTA SEMARANG - Kang Andini Wulandari; Galuh Wilujeng Saraswati; Farah Yuniar Alin Raihatuzzahra (LPPM ITB AAS Indonesia Surakarta, 2023)
Handling household waste is an important aspect in maintaining environmental cleanliness and public health. However, challenges in waste management often arise at various levels. In 2022, the amount of waste generated in Indonesia will be 68.7 million tons dominated by organic waste. Approximately 38.28% of this waste comes from households. The new waste management model is to reduce and handle waste (RI Law No. 18 of 2008) which is integrated from upstream to downstream with community participation, especially households, as the largest producers of waste generation. Therefore, the community must minimize waste generation and have the capacity and knowledge to manage the waste produced well. This service aims to analyze management assistance for household waste management in Sambiroto Village, Tembalang District, Semarang City. The implementation method is carried out in stages, starting with conducting a Focus Group Discussion (FGD) regarding the situation in the field, identifying problems, preparing material and selecting resource persons. The results of this assistance show an increase in community participation in waste management. Awareness of the importance of waste sorting is increasing, and people are starting to adopt the practice of waste sorting in households. However, there are still obstacles in terms of adequate waste management infrastructure and coordination between various stakeholders.